2020
DOI: 10.1080/1540496x.2020.1784717
|View full text |Cite
|
Sign up to set email alerts
|

Household Financial Decision Making Amidst the COVID-19 Pandemic

Abstract: This paper investigates the impact of the COVID-19 pandemic on household investment decisions using a novel survey conducted by the Survey and Research Center for China Household Finance. We use linear probability and probit models to analyze the effects of COVID-19 at the household level. Our results show that households who know someone infected with COVID-19 lose confidence in the economy. They are more likely to change their risk behavior and become risk-averse. Further, COVID-19 increases the probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
98
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 28 publications
4
98
2
2
Order By: Relevance
“…In closing this introduction, we note that research on COVID-19 and economic and financial systems is at a nascent stage. This literature has 2020); household decision making (Yue et al 2020); and firm performance (Shen et al 2020;Fu and Shen 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In closing this introduction, we note that research on COVID-19 and economic and financial systems is at a nascent stage. This literature has 2020); household decision making (Yue et al 2020); and firm performance (Shen et al 2020;Fu and Shen 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, we examine whether market volatility at the Asian regional level can explain stock market volatility at the country-level. Recent studies have shown that the COVID-19 pandemic has significantly affected global economies; see, for instance, Mishra et al (2020), Salisu & Akanni (2020), Chen et al (2020), Wang et al (2020), Yue et al (2020), Yu et al (2020), Xiong et al (2020), Shen et al (2020), Gu et al (2020), Haroon & Rizvi (2020), Iyke (2020), He et al (2020), and Liu et al (2020). According to Sha & Sharma (2020) and Phan & Narayan (2020), the COVID-19 pandemic represents the largest and most disturbing shock to the global economic system and it is therefore important to understand whether the country level volatility can be determined by the regional level stock market volatility.…”
Section: Introduction I Introductionmentioning
confidence: 99%
“…Few researchers have investigated the impact of this pandemic on households' financial behaviors in emerging markets. And the existing limited studies using household survey data mainly discuss the impact of the COVID-19 pandemic on household consumption and portfolio choice (Liu, Pan, and Yin 2020;Yue, Korkmaz, and Zhou 2020).…”
Section: Introductionmentioning
confidence: 99%